PERLINDUNGAN HUKUM TERHADAPANAK OLEH PEMERINTAH PROVINSI KEPULAUAN RIAU PADA MASA PANDEMI COVID-19 DENGAN KOSONGNYA KOMISIONER KPPAD - Twina Nurul Ariestiana; Rasji Rasji (Jurnal Hukum Adigama, 2022)
In providing legal protection for children, the state has ratified Law No. 35 of 2014 which is anamendment to Law No. 23 of 2022 regarding Child Protection. The method in this study applies thenormative legal method which is supported by empirical law. The normative legal research methodis a method used to conduct a study of an existing written legal material. In this study, it was foundthat during the Covid-19 pandemic, with the vacancy of the KPPAD commissioner, from a securityperspective, a safety guarantee was also provided for victim witnesses and reporters, bothphysically, mentally or socially. In this case, information is given to the victim/victim's familyregarding the progress of the outcome of the ongoing case in the District Court until the completionof the process. In addition to physical and mental protection, the provision of restitution andmaterial compensation is also very much needed by the victim/victim's family, considering thevictims of crimes against children during the Covid-19 Pandemic. The impact of the vacancy of theKPPAD commissioner on child protection carried out by the Riau Islands Provincial Government during the Covid-19 pandemic, among others, the many cases that were not handled by the UPTDand the Police due to the increasing crime rate. cases involving children as victims. Victims(children) have suf ered for years because they do not dare to report, they are afraid that if victims(children) report they will be psychologically intimidated by irresponsible parties.